Conversion of waste Polyethylene Terephthalate PET Polymer into activated carbon and its feasibility to produce green fuel - Ahmad Ahangar, Firdous; Rashid, Umer; Ahmad, Junaid; Tsubota, Toshiki; Alsalme, Ali (Multidisciplinary Digital Publishing Institute, 2021)
In this study, a novel idea was proposed to convert the polyethylene terephthalate (PET) waste drinking-water bottles into activated carbon (AC) to use for waste cooking oil (WCO) and palm fatty acid distillate (PFAD) feasibility to convert into esters. The acidic and basic char were prepared by using the waste PET bottles. The physiochemical properties were determined by employing various analytical techniques, such as field emission scanning electron microscopy (FESEM), thermogravimetric analysis (TGA), Fourier transform infrared (FTIR), Brunauer–Emmett–Teller (BET) and temperature-programmed desorption – ammonia/carbon dioxide (TPD-NH3/CO2). The prepared PET H3PO4 and PET KOH showed the higher surface area, thus illustrating that the surface of both materials has enough space for impregnation of foreign precursors. The TPD-NH3 and TPD-CO2 results depicted that PET H3PO4 is found to have higher acidity, i.e., 18.17 mmolg−1, due to the attachment of phosponyl groups to it during pretreatment, whereas, in the case of PET KOH, the basicity increases to 13.49 mmolg−1. The conversion results show that prepared materials can be used as a support for an acidic and basic catalyst for the conversion of WCO and PFAD into green fuel.